STUDI FENOMENOLOGI TERAPI OKUPASI BAGI PENYANDANG SKIZOFRENIA DI UPTD LIPONSOS SURABAYA - Rizki Dwi Bachtiar Surin; Igaa Noviekayati; Niken Titi Pratitis (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2024)
Background: This study explores the subjective experiences of individuals with schizophrenia regarding occupational therapy through the framework of Activity Daily Living (ADL) at UPTD LIPONSOS, Surabaya. Using a phenomenological approach. Objective: The study aims to explore the subjective experiences of individuals with schizophrenia regarding occupational therapy through the ADL framework at UPTD LIPONSOS, Surabaya. Method: This study employs a phenomenological approach to understand the personal and subjective experiences of patients. Out of 140 individuals with schizophrenia (ODS) with low ADL levels, six were selected for intervention based on specific criteria such as residual schizophrenia diagnosis and low aggression levels. Data were collected through semi-structured in-depth interviews and participant observation. Results: Occupational therapy enhances independence, self-esteem, and emotional management for individuals with schizophrenia, providing hope and motivation, and strengthening social relationships through personalized approaches and strong social support. Conclusion: This study highlights the importance of personalized approaches in occupational therapy. The findings contribute to the development of more effective and evidence-based interventions, focusing on improving the quality of life for individuals with schizophrenia. This approach not only enhances independence and self-esteem but also provides hope and motivation for a better future.